Reasoning as a Crosscutting in the Construction of Thought Logical (2016)
In this article disclosed forms of intuitive reasoning employed by the 5th grade students of the Institución Educativa Rural del Sur in the classroom; to identify these forms, three stages were developed initially population recognition took place; secondly, they were observed and some kinds of subjects such as Spanish, English and mathematics, in which the main forms of everyday language used by students in the classroom were identified were recorded: attribution of meaning and interaction; finally, based on the approach of grounded theory, information collected in the Atlas.ti software in order to identify emerging categories and inductive present between the data and their respective relationships, which revealed forms analyzed reasoning; it was established that students who participated in the research used mainly paraphrasing and apposition as a form of everyday reasoning also noted that the experience was a major influence on the interpretation of environmental situations.